Evidencing decadal and interdecadal hydroclimatic variability over the Central Andes - Segura Cajachagua, Hans Mikhail (2016)
In this study we identified a significant low frequency variability (8 to 20 years) that characterizes the hydroclimatology over the Central Andes. Decadal–interdecadal variability is related to the central-western Pacific Ocean (R² = 0.50) and the zonal wind at 200 hPa above the Central Andes (R² = 0.66). These two oceanic–atmospheric variables have a dominant decadal–interdecadal variability, and there is a strong relationship between them at a low frequency time scale (R² = 0.66). During warming decades in the central-western Pacific Ocean, westerlies are intensified at 200 hPa above the Central Andes, which produce decadal periods of hydrological deficit over this region. In contrast, when the central-western Pacific Ocean is cooler than usual, easterly anomalies prevail over the Central Andes, which are associated with decades of positive hydrological anomalies over this region. Our results indicate that impacts of El Niño on hydrology over the Central Andes could be influenced by the low frequency variability documented in this study.